ChemInform Abstract: Layered Oxychlorides [PbBiO2] An+1BnO3n—1Cl2 (A: Pb/Bi, B: Fe/Ti): Intergrowth of the Hematophanite and Sillen Phases. Issue 27 (18th June 2015) - Batuk, Maria; Batuk, Dmitry; Tsirlin, Alexander A.; Filimonov, Dmitry S.; Sheptyakov, Denis V.; Frontzek, Matthias; Hadermann, Joke; Abakumov, Artem M.
Abstract The title compounds are prepared by solid state reaction of stoichiometric mixtures of PbO, PbCl2, Bi2O3, BiOCl, Fe2O3, and TiO2 (evacuated quartz tubes, 650 °C, 7 h; annealing at 750 °C, 20 h).